Suphistic Education: the Basis of Character Muhammadiyah's Struggle - Samsurizal, Samsurizal; Mardiana, Puja Dikusuma; Pasaleron, Roni; Ohira, Norman; Busmayaril, Busmayaril (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2023)
Muhammadiyah is one of the largest religious organizations in Indonesia, and it has had a significant influence both domestically and abroad. The organization has developed a unique approach to carrying out its mission, including Islamic spirituality, law, and ethics. Examining the basic character of Muhammadiyah's struggle requires in-depth analysis to obtain a complete and representative picture. This research aims to collect comprehensive information regarding the basics of Sufistic education which is the basis of Muhammadiyah's struggle. This research uses qualitative research methods with a thematic analysis approach with research steps; i) understand the data, ii) find the main themes, and iii) look for themes related to the research. The researchers' data sources were obtained from online and offline literature, books, the web, articles, and others. Then, analyze the data obtained by describing, then validating the accuracy of the data comprehensively and completely according to research needs. The research findings found that Sufistic Education was the basis for the struggle of the Muhammadiyah organization, understood from the five principles of good Muhammadiyah which were first taught during the founding of this organization, namely Ahmad Dahlan regarding religious principles (beliefs), legal regulations (sharia) and noble character (akhlaq al-karimah). This was developed in its philosophical delivery with a Sufistic touch. It is hoped that this research can provide critical and understandable information and become a related reference.